Zambia : Ex Post Assessment of Longer-Term Program Engagement: Update. (IMF Staff Country Reports; Country Report ;, 2011)
Despite improved economic growth, poverty in Zambia remained formidable and called for fiscal consolidation to contain the domestic debt and interest payments that jeopardized macroeconomic stability and social spending. Macroeconomic outcomes during ECF-2 were particularly strong. The global financial crisis significantly affected copper prices. Laying the groundwork to sustain low inflation, infrastructure development, mobilizing domestic revenues, and financial sector development are priority areas for future programs. A well-articulated medium-term economic program would help Zambia to strengthen resilience and raise growth rates.